Construction of highly water-stable metal-organic framework UiO-66 thin-film composite membrane for dyes and antibiotics separation - Fang, Si-Yuan; Zhang, Peng; Gong, Ji-Lai; Tang, Lin; Zeng, Guang-Ming; Song, Biao; Cao, Wei-Cheng; Li, Juan; Ye, Jun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
[Display omitted] •Highly water-stable and negatively charged UiO-66 TFC membrane was constructed.•The TFC membrane showed high permeability and selectivity for dye and antibiotic.•Antifouling property of UiO-66 TFC membrane presented FRR values higher than 92%.•Size exclusion and electrostatic interaction of UiO-66 TFC membrane were elaborated. Metal-organic frameworks (MOFs) materials show great potential in wastewater separation applications. In this study, zirconium-based MOFs (UiO-66) were prepared and constructed universal, high-performance, and flexible nanofiltration (NF) membrane for various dyes and antibiotics separation. The substrate was constructed by two-steps, a) doping graphene oxide (GO) sheets into the membrane casting solution containing polyacrylonitrile (PAN) and forming 2D-3D connecting pores by phase immersion conversion method (defined as GO@PAN), b) immersing the GO@PAN substrate into dopamine solution to self-polymerize into chain macromolecules, which obtaining good compatible and flexible substrate (defined as PGP). Moreover, the UiO-66 was synthesized via solvothermal method and subsequently coated onto the PGP substrate by vacuum-assisted filtration. Benefiting from the water stability, porous structure, and negative charge of UiO-66, the outstanding filtration performance of the UiO-66/PGP thin-film composite (TFC) membrane was achieved. The pure water permeability of the UiO-66/PGP TFC membrane was 31.33 ± 0.75 L m−2h−1 bar−1, and the rejection rates for dye (Congo red, Methyl orange, Rhodamine B, and Methylene blue) and antibiotic (Tetracycline hydrochloride, Oxytetracycline, and Ciprofloxacin) were above 94%. Therefore, we further explored the retention mechanism of the UiO-66/PGP TFC membrane for dye and antibiotic separation (size exclusion and electrostatic interaction). More importantly, antifouling properties and long-time stability of the UiO-66/PGP TFC membrane were also evaluated. These results indicated that the prepared UiO-66/PGP TFC membrane is promising for wastewater treatment, separation, and purification in many industrial and pharmaceutical fields.